2010
DOI: 10.1111/j.1751-0813.2010.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of diclofenac sodium and flunixin meglumine as adjuncts to antibacterial treatment of respiratory disease of calves

Abstract: In this trial, a single intramuscular dose of diclofenac sodium was equally effective as three intravenous injections of flunixin meglumine given on consecutive days as adjunctive therapy for BRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 11 publications
2
12
0
1
Order By: Relevance
“…Non-steroidal anti-inflammatory drugs (NSAIDs) have shown to reduce pyrexia [88][89][90][91], clinical signs [89,90], and lung pathology [90][91][92], and improve average daily weight gains [92] in calves with respiratory disease compared to untreated calves or calves only treated with antimicrobials. Other studies, however, have not found significant differences between treatment groups [93,94].…”
Section: Treatmentmentioning
confidence: 99%
“…Non-steroidal anti-inflammatory drugs (NSAIDs) have shown to reduce pyrexia [88][89][90][91], clinical signs [89,90], and lung pathology [90][91][92], and improve average daily weight gains [92] in calves with respiratory disease compared to untreated calves or calves only treated with antimicrobials. Other studies, however, have not found significant differences between treatment groups [93,94].…”
Section: Treatmentmentioning
confidence: 99%
“…dose of DCF was equally effective as three intravenous (i.v.) injections of flunixin meglumine given on consecutive days as an adjunct to antibacterial treatment of calves with bovine respiratory disease (BRD) (Guzel, Karakurum, Durgut, & Mamak, 2010). Frisbie, McIlwraith, Kawcak, Werpy, and Pearce (2009) reported that treatment with DCF liposomal cream by topical administration had significant benefit and no detrimental effects for horses with osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the use of non-steroidal anti-inflammatory drugs (NSAIDs) is considered essential for the treatment of BRD-affected calves (Lekeux, 2007;Guzel et al, 2010;Lekeux and Wallemacq, 2010). An additional benefit is the reduction of fever, pain and discomfort, which leads to improved food intake and welfare (Lockwood et al, 2003).…”
Section: Other Diseases In Beef Cattlementioning
confidence: 99%